Learning from media : arguments, analysis, and evidence - Clark, Richard E. 1940- (Emerald Publishing Limited : Information Age Publishing, 2012)
Richard Clark's observation that "...media are mere vehicles that deliver instruction but do not influence student achievement any more than the truck that delivers our groceries causes changes in our nutrition" is as misunderstood today as it was when first published in the Review of Educational Research in 1983. The convincing if little read scientific evidence presented by Clark has divided the field and caused considerable concern, especially among the providers of newer media for learning.A collection of writings about the "media effects debate," as it has come to be called, was published in 2001. Edited by Clark, Learning From Media was the first volume in the series "Perspectives in Instructional Technology and Distance Education." The series editors are convinced that the writings of Clark and those who take issue with his position are of critical importance to the field of instructional technology, Thus, a revised, second edition of Learning From Media is now being offered.The debate about the impact of media on learning remains a fundamental issue as new mediated approaches to teaching and learning are developed, and Clark's work should be at the center of the discussion. The critical articles on both sides of this debate are contained in Learning From Media, 2nd Edition.
Keywords: Media programs (Education); Education -- Administration -- General.; Open learning, distance education.; Educational administration and organization.; elektronické knihy; electronic books